Analisis Pemahaman Konsep Siswa SMP pada Materi Aljabar - Indah Rohmatu Febrian Fitriani; Wilda Mahmudah (Departement of Mathematics Education, 2024)
Understanding algebra concepts necessary in learning mathematics. However, unfortunately there are still students who have difficulty understanding the mathematical concepts of algebra material. The aim research is to find out how students understand the mathematical concepts of algebra material at Nurul Hidayah Islamic Middle School. This research quantitative descriptive. The instruments essay questions and data collection using written tests. The research results show that students' conceptual understanding high category 38%, medium category 38%, low category 8% and very low category 15%. The research results also showed that students' conceptual understanding first indicator 84.62%, included high criteria, the second indicator 76.92%, included in the high criteria, the third indicator 90.38%, included the high criteria. Included very high criteria, the fourth indicator 50.00% is included low criteria, the fifth indicator 32.69% is included very low criteria, the sixth indicator 36.54% is included very low criteria. and the seventh indicator 40.38% is included low criteria. Students' conceptual understanding of several indicators is still low, namely the fourth, fifth, sixth and seventh indicators, so teachers need to pay more attention to these indicators so that students can understand algebraic concepts.